A SYSTEMATIC REVIEW ON CROSS BORDER ENTREPRENEURSHIP - GEOGRAPHICAL, THEORETICAL AND METHODOLOGICAL GAPS - Masitah Afandi; Mohd Rafi Yaacob (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Cross Border Entrepreneurship (CBE) contributes to regional economic development through international opportunities recognition and exploitation. This study tends to explore and review the CBE literature to find the gaps by systematically investigating the existing literature guide by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) statement. This study emphasis on the country’s classification, perspective area, methods of study, as well as underpinning theories. It reveals 32 relevant research topics of the literature of CBE and highlights four main gaps. First, previous studies of CBE are yet to explore extensively in transition and developing countries. Second, areas of study lack focus on the process of identifying critical issues of CBE. Third, qualitative strategies which enable the specification of new output findings of the CBE are yet explored. Lastly, experiential learning theory, agency theory, financial theory, cash flow theory, locational condition theory, behavioural internationalization process theory, entrepreneurial opportunities theory, and human capital theory yet be utilized and diversified to develop a new understanding of a variety of challenging phenomena in the CBE studies.